Pengaruh Return on Equity, Non Performing Loan, dan Loan to Deposit Ratio Terhadap Harga Saham - Ayu Faraghita; Andar Febyansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to determine the effect of Return on Equity, Non Performing Loan and Loan to Deposit Ratio on Stock Prices in the Banking sector listed on the Indonesia Stock Exchange for the period 2021-2023. The implementation of this study uses an associative causality research design with secondary data types. The sampling technique used purposive sampling and obtained 30 companies that met the criteria from the population with a research period of 3 years, so that 90 sample data were obtained. This study uses a multiple linear regression analysis model. The results of the study show that Return on Equity has a positive effect on Stock Prices, Non Performing Loans have a negative effect on Stock Prices and Loan to Deposit Ratio has a negative effect on Stock Prices. Further researchers are expected to consider or add other variables that can affect Stock Prices such as Sales Growth, Dividend Policy, Inflation Rates and Interest Rates on different research objects. The implications in this study found that the ROE, NPL and LDR factors can be used as the main reference for Banking in an effort to increase Banking Stock Prices.